Preventing Identity Theft: Perspectives on Technological Solutions from Industry Insiders - Piquero, Nicole Leeper (Victims & offenders, 2021)
An estimated 26 million American citizens per year have been victims of an identity-based crime. This study contributes to the scholarship on financial crimes facilitated through identity-based criminal activity by examining the views on technological approaches to the prevention of identity theft among 50 professionals working in the identity-based crime victim services, including those from the public sector and private industry. The professionally diverse sample included private investigators, fraud examiners, victim service providers, and executives of firms offering victim services and protection services. Data were collected during a series of focus groups held at professional conferences. The paper reports on the views held by focus group participants on specific technological solutions to identity theft victimization, including biometric scanning, dark web scanning, subscription -based monitoring programs, and broader thematic observations about the current environment for protecting information, emerging sources of risk, and policy recommendations identified by focus group participants. Perspectives from insiders about the pros and cons of each approach can provide researchers and enforcement agencies with enhanced capacity to avoid empty technological promises that fail to protect victims from subsequent victimizations.